Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment
By doping rare earth elements and transition elements into NiFeMn positive electrode active material to form a dense doping layer, the problem of low capacity retention of layered transition metal oxide batteries is solved, and the stability and capacity retention of the battery are significantly improved.
Patent Information
- Application Number
- CN202310736859.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-20
AI Technical Summary
The capacity retention rate of existing layered transition metal oxide sodium ion batteries is low, mainly due to structural damage caused by water vapor invasion, lattice oxygen precipitation and sodium ion detachment.
NiFeMn is used as the main material, doping rare earth element M1 and transition element M2 to form a dense and uniform doping layer to prevent water vapor from invasion, inhibit lattice oxygen precipitation and sodium ion detachment, and improve the structure and cyclic stability of the material.
The capacity retention rate of the battery is significantly improved, and the ratio control of the rare earth element M1 and Mn and the chemical bond formation of the doped element M2 is enhanced, which enhances the air stability and cyclic stability of the positive electrode active material.
Smart Images

Figure CN119170797A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] Secondary batteries are not only used in energy storage power systems such as hydropower, thermal, wind and solar power stations, but are also widely used in electric transportation vehicles such as electric bicycles, electric motorcycles, electric cars, as well as in military equipment, aerospace and other fields.
[0003] Sodium ion battery is a kind of secondary battery, and layered transition metal oxide is a commonly used positive electrode active material for sodium ion battery. However, the capacity retention rate of existing sodium ion batteries containing layered transition metal oxide is low.
[0004] Public Content
[0005] In view of the technical problems existing in the background technology, the present application provides a positive electrode active material, aiming to solve the problem of low capacity retention rate of batteries containing the positive electrode active material.
[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a positive electrode active material, wherein the positive electrode active material comprises:
[0007] Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f ,
[0008] Wherein, M1 includes rare earth elements, M2 includes at least one of Group IA elements, Group IIA elements, Group IIIA elements, Group IVA elements, Group VA elements, Group VIA elements and transition elements, 0.6≤x≤1.2, 0<a≤0.5, 0<b≤0.4, 0.3≤c≤0.75, 0.001≤d≤0.05, 0≤e≤0.3, -0.1≤δ≤0.1, 0≤f≤0.1, 0.005≤d / c≤0.05, a+b+c+d+e=1.
[0009] The present application includes at least the following beneficial effects: the main material of the positive electrode active material of the present application includes NiFeMn, and is doped with rare earth element M1 and doping element M2, and the above content of Fe can improve the specific capacity of the material. The rare earth element M1 has a large radius and will form a dense and uniform doping layer on the surface of the positive electrode active material. The doping layer can effectively block the intrusion of water vapor from the surface of the positive electrode active material to the bulk phase, thereby improving the structural stability of the material. During high-voltage charging, the doping layer can also inhibit the precipitation of lattice oxygen and the penetration of electrolyte into the material, thereby improving the structural stability of the material and improving the capacity retention rate of the battery containing it. The doping element M2 is distributed in the bulk phase of the positive electrode active material, and can form a strong chemical bond with O in the positive electrode active material, inhibit the release of Na ions in the positive electrode active material from the bulk phase, and can reduce the change in the interlayer spacing of the positive electrode active material, delay the occurrence of phase change, and improve the cycle stability of the positive electrode active material, thereby improving the capacity retention rate of the battery. In addition, the ratio d / c of the rare earth element M1 to Mn in the positive electrode active material is within the above range, which is beneficial to improving the air stability and cycle stability of the positive electrode active material, thereby improving the capacity retention rate of the battery containing the same.
[0010] In some embodiments of the present application, the rare earth element includes at least one of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu. Thus, M1 uses at least one of the above rare earth elements to form a dense and uniform doping layer on the surface of the positive electrode active material, reducing the probability of phase change of the positive electrode active material, improving the cycle performance of the positive electrode active material, and thus improving the capacity retention rate of the battery containing it.
[0011] In some embodiments of the present application, the M2 includes at least one of B, Mg, Al, Si, K, Ca, Ga, Ge, Se, Rb, Sr, In, Sn, Sb, Te, Sc, Ti, V, Cr, Co, Cu, Zn, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, Hf, Ta, W, Re, Os, Ir, Pt and Au. Thus, the element M2 is uniformly distributed in the bulk phase of the positive electrode active material, and can form a strong chemical bond with O in the positive electrode active material, inhibiting the release of the Na element in the positive electrode active material from the bulk phase, thereby improving the air stability of the positive electrode active material, thereby improving the capacity retention rate of the battery containing it.
[0012] In some embodiments of the present application, 0.01≤d / c≤0.03, which is beneficial to improve the air stability and cycle stability of the positive electrode active material, thereby improving the capacity retention rate of the battery containing the same.
[0013] In some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions: 0.1≤a≤0.4, optionally 0.15≤a≤0.3; 0.1≤b≤0.35, optionally 0.15≤b≤0.35; 0.35≤c≤0.6, optionally 0.35≤c≤0.5.
[0014] In some embodiments of the present application, 1.75≤(a+b+c) / b≤9.5, optionally, 2≤(a+b+c) / b≤9.5, and more optionally, 2≤(a+b+c) / b≤6.3. Thus, in the positive electrode active material, the ratio of the sum of the contents of Ni, Fe and Mn to the content of Fe is within the above range, which is conducive to improving the air stability and cycle stability of the positive electrode active material, thereby improving the capacity retention rate of the battery containing it.
[0015] In some embodiments of the present application, 0.8<x≤1.0, the phase of the positive electrode active material includes O3 phase, the space group includes R3m, and the interlayer spacing is 0.53nm-0.55nm. Therefore, when x is within the above range, the Na content of the positive electrode active material of the formed O3 phase is high, which can improve the capacity of the battery.
[0016] In some embodiments of the present application, 0.6≤x≤0.8, the phase of the positive electrode active material includes a P2 phase, the space group includes P63 / mmc, and the interlayer spacing is 0.54nm-0.57nm. Thus, when x is within the above range, the interlayer spacing of the formed P2 phase positive electrode active material is large, which can improve the rate performance and cycle performance of the battery.
[0017] In some embodiments of the present application, the pH value of the immersion solution of the positive electrode active material is less than or equal to 13. Optionally, the pH value of the immersion solution of the positive electrode active material is less than or equal to 12.7. More optionally, the pH value of the immersion solution of the positive electrode active material is 11.0≤pH≤12.7.
[0018] In some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions:
[0019] The positive electrode active material D v 50 is 3μm-30μm, optional is 5μm-15μm;
[0020] The specific surface area of the positive electrode active material is 0.1 m 2 / g-5m 2 / g, optional 0.3m 2 / g-3m 2 / g;
[0021] The tap density of the positive electrode active material is 1 g / cm 3-3g / cm 3 , optional 1.5g / cm 3 -2.5g / cm 3 ;
[0022] The compaction density of the positive electrode active material under a pressure of 300 MPa is 3.0 g / cm 3 -4.0g / cm 3 .
[0023] Therefore, when the D of the positive electrode active material v 50. When at least one of the specific surface area, tap density and compaction density under a pressure of 300 MPa is within the above range, the conduction distance of Na ions in the positive electrode active material is small and the surface side reactions are small, which promotes the positive electrode active material to exert its gram capacity and improves the capacity retention rate of the battery containing it.
[0024] The second aspect of the present application provides a method for preparing the positive electrode active material according to the first aspect, comprising:
[0025] Mixing a Na source, a Ni source, a Fe source, a Mn source, an M1 source, and an M2 source to obtain a precursor;
[0026] The precursor is calcined to obtain a positive electrode active material.
[0027] Therefore, the positive electrode active material prepared in the present application has excellent air stability and cycle stability, and the battery containing the positive electrode active material has excellent capacity retention rate.
[0028] The third aspect of the present application provides another method for preparing the positive electrode active material described in the first aspect, comprising:
[0029] Mixing a Ni source, a Fe source, a Mn source, a M1 source, and a M2 source with water to obtain a mixed solution;
[0030] reacting the solution with a precipitant to obtain a precursor;
[0031] The precursor is mixed with a Na source and then calcined to obtain a positive electrode active material.
[0032] Therefore, the positive electrode active material prepared in the present application has excellent air stability and cycle stability, and the battery containing the positive electrode active material has excellent capacity retention rate.
[0033] The fourth aspect of the present application provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present application, the positive electrode active material prepared by the method described in the second aspect, or the positive electrode active material prepared by the method described in the third aspect.
[0034] The fifth aspect of the present application provides a battery, which comprises the positive electrode sheet described in the fourth aspect of the present application. Thus, the battery has an excellent capacity retention rate.
[0035] A sixth aspect of the present application provides an electrical device, which includes the battery described in the fifth aspect.
[0036] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0038] Figure 1 is a schematic structural diagram of a battery according to one embodiment of the present application;
[0039] Figure 2 is a schematic structural diagram of a battery module according to an embodiment of the present application;
[0040] Figure 3 is a schematic structural diagram of a battery pack according to an embodiment of the present application;
[0041] Figure 4 yes Figure 3 Exploded diagram of
[0042] Figure 5 is a schematic diagram of an embodiment of an electrical device in which a battery is used as a power source;
[0043] Figure 6 is the XRD diagram of the positive electrode active material of Example 1 and Comparative Example 1 of the present application;
[0044] Figure 7 is the XRD diagram of the positive electrode active material of Example 1 and Comparative Example 2 of the present application;
[0045] Figure 8 It is a charging and discharging diagram of the positive electrode sheet of Example 1 of the present application at 1.5-4.2 / 4.2-1.5V;
[0046] Fig. 9 It is a comparison chart of the capacity retention rate of the batteries of Example 1 and Comparative Example 4 of the present application.
[0047] Description of reference numerals:
[0048] 1: Secondary battery; 2: Battery module; 3: Battery pack; 4: Upper case; 5: Lower case. DETAILED DESCRIPTION
[0049] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0050] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0051] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0052] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0054] With the technological development and increasing demand for electric vehicles and rechargeable mobile devices, secondary batteries, as a representative of the new energy field, have also seen rapid development in related research. Compared with traditional lithium-ion batteries, sodium-ion batteries have a strong price advantage and have broad application prospects in large-scale power storage systems.
[0055] Layered transition metal oxides have become one of the popular positive electrode active materials for sodium-ion batteries due to their high electrical conductivity, high energy density, large capacity and long cycle life.
[0056] However, existing layered transition metal oxides have the following problems: on the one hand, water vapor in the air will intrude from the surface of the layered transition metal oxide to the bulk phase, causing the structure of the layered transition metal oxide to be easily destroyed after being exposed to air for too long; on the other hand, during high-voltage charging, the oxygen coordinated with the metal in the layered transition metal oxide will also undergo an oxidation reaction, that is, lattice oxygen release will occur, causing the material structure to be destroyed; on the other hand, during high-voltage charging, cracks will be generated in the layered transition metal oxide due to the phase change accompanied by the release of sodium ions, and the electrolyte will penetrate into the material from the cracks to react and deteriorate the material structure. The destruction of the structure of the layered transition metal oxide material leads to poor stability of the material, which directly leads to a low capacity retention rate of the battery.
[0057] In the present application, the positive electrode active material is based on NiFeMn and doped with rare earth element M1 and doping element M2 and the ratio of rare earth element M1 to Mn is controlled. On the one hand, the rare earth element M1 has a large radius and will remain on the surface of the positive electrode active material, and form a dense and uniform doping layer on the surface of the positive electrode active material. The doping layer can effectively block the intrusion of water vapor from the surface of the positive electrode active material to the bulk phase, thereby improving the structural stability of the material. In addition, during high-voltage charging, the doping layer can also inhibit the precipitation of lattice oxygen and the penetration of electrolyte into the material, thereby improving the structural stability of the material and improving the capacity retention rate of the battery containing it; on the other hand, the doping element M2 is distributed in the bulk phase of the positive electrode active material, and can form a strong chemical bond with O in the positive electrode active material, inhibiting the release of Na ions in the positive electrode active material from the bulk phase, and can reduce the change in the interlayer spacing of the positive electrode active material, delay the occurrence of phase change, and improve the cycle stability of the positive electrode active material. In addition, in the present application, the ratio d / c of the rare earth element M1 to Mn in the positive electrode active material is controlled at 0.005-0.05, which is beneficial to improving the air stability and cycle stability of the positive electrode active material, thereby improving the capacity retention rate of the battery containing it.
[0058] The positive electrode active material disclosed in the embodiment of the present application is suitable for secondary batteries, and the battery disclosed in the embodiment of the present application can be used in electrical equipment using the battery as a power source or various energy storage systems using the battery as an energy storage element. Electrical equipment may include, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, and the like.
[0059] In a first aspect, the present application provides a positive electrode active material, the positive electrode active material comprising:
[0060] Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f ,
[0061] Wherein, M1 includes rare earth elements, M2 includes at least one of Group IA elements, Group IIA elements, Group IIIA elements, Group IVA elements, Group VA elements, Group VIA elements and transition elements, 0.6≤x≤1.2, 0<a≤0.5, 0<b≤0.4, 0.3≤c≤0.75, 0.001≤d≤0.05, 0≤e≤0.3, -0.1≤δ≤0.1, 0≤f≤0.1, 0.005≤d / c≤0.05, a+b+c+d+e=1.
[0062] The present application includes at least the following beneficial effects: the main material of the positive electrode active material of the present application includes NiFeMn, and is doped with rare earth element M1 and doping element M2, and the above-mentioned content of Fe can improve the specific capacity of the positive electrode active material. The rare earth element M1 has a large radius, and will form a dense and uniform doping layer on the surface of the positive electrode active material. The doping layer can effectively block the intrusion of water vapor from the surface of the positive electrode active material to the bulk phase, and improve the structural stability of the material. During high-voltage charging, the doping layer can also inhibit the precipitation of lattice oxygen and the penetration of electrolyte into the material, thereby improving the structural stability of the material and improving the capacity retention rate of the battery containing it. The doping element M2 is distributed in the bulk phase of the positive electrode active material, and can form a strong chemical bond with O in the positive electrode active material, inhibit the release of Na ions in the positive electrode active material from the bulk phase, and can reduce the change in the interlayer spacing of the positive electrode active material, delay the occurrence of phase change, and improve the cycle stability of the positive electrode active material, thereby improving the capacity retention rate of the battery.
[0063] In addition, the ratio d / c of the rare earth elements M1 and Mn in the positive electrode active material is within the above range, which can reduce the insufficient solid solubility between the rare earth elements and Mn, resulting in the rare earth elements agglomerating on the surface of the positive electrode active material to form a mixed phase, and at the same time reduce the probability of not being able to generate a rare earth doping layer due to insufficient rare earth elements, which is conducive to the rare earth elements forming a dense and uniform rare earth doping layer on the surface of the positive electrode active material, effectively blocking the invasion of water vapor from the surface of the positive electrode active material to the bulk phase, and can also inhibit the precipitation of lattice oxygen and the penetration of electrolyte into the bulk phase, thereby improving the air stability and cycle stability of the positive electrode active material, thereby improving the capacity retention rate of the battery containing it.
[0064] In summary, the main material in the positive electrode active material includes NiFeMn, and is doped with rare earth element M1 and doping element M2, and the doping amount and d / c of each element are controlled. In general, the above characteristics work together to improve the specific capacity of the positive electrode active material.
[0065] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f Here, x can be 0.6≤x≤1.2, such as 0.7≤x≤1.1, 0.8≤x≤1, 0.9≤x≤1.1, 1≤x≤1.1, etc. Thus, the positive electrode active material includes the sodium element in this content, so that the battery has a higher capacity.
[0066] It should be noted that in the positive electrode sheet, battery or electrical device, as the battery undergoes formation and circulation processes, sodium ions will be consumed, so the measured sodium content x in the positive electrode active material may be less than 1. At the same time, if the positive electrode sheet and the negative electrode sheet use a sodium supplement, the measured sodium content x in the positive electrode active material may be greater than 1 after the battery undergoes formation and circulation processes.
[0067] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f Where a can be 0<a≤0.5, for example, 0.001≤a≤0.5, 0.005≤a≤0.5, 0.1≤a≤0.5, 0.15≤a≤0.45, 0.2≤a≤0.4, 0.25≤a≤0.35, 0.25≤a≤0.3, etc. Thus, the positive electrode active material includes this content of nickel, which can improve the energy density of the battery. In other embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f Here, a can be 0.1≤a≤0.4, for example, 0.15≤a≤0.3.
[0068] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f Where b can be 0<b≤0.4, for example, 0.001≤a≤0.4, 0.005≤a≤0.4, 0.1≤a≤0.4, 0.15≤a≤0.35, 0.2≤a≤0.35, 0.25≤a≤0.35, 0.3≤a≤0.35, etc. Therefore, in the process of Na ions being extracted from the material, Fe as a charge-compensating metal element will be oxidized from a trivalent state to a tetravalent state. When Na ions are reinserted into the material, Fe will be reduced from a tetravalent state to a trivalent state. The positive electrode active material includes this content of Fe, which can increase the specific capacity of the material. In other embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f Here, b can be 0.1≤b≤0.35, for example, 0.15≤b≤0.35.
[0069] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f Where c can be 0.3≤c≤0.75, for example, 0.35≤c≤0.75, 0.4≤c≤0.7, 0.45≤c≤0.65, 0.5≤c≤0.6, 0.55≤c≤0.6, etc. Thus, this content of Mn can be dissolved with the rare earth element M1 to form a uniform and dense doping layer on the surface of the positive electrode active material, thereby improving the structural stability of the positive electrode active material, thereby improving the capacity retention rate of the battery containing it. In other embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f Here, c can be 0.35≤c≤0.6, for example, 0.35≤c≤0.5.
[0070] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f M1 includes at least one of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu. Thus, the M1 of this composition can form a dense and uniform doping layer on the surface of the positive electrode active material, which can effectively block the intrusion of water vapor from the surface of the positive electrode active material to the bulk phase, and improve the structural stability of the material. At the same time, during the high-voltage charging process, the doping layer of this composition can also inhibit the precipitation of lattice oxygen and the penetration of electrolyte into the material, improve the structural stability of the material, and thus improve the capacity retention rate of the battery containing it.
[0071] In addition, M1 adopts at least one of the above elements, which is environmentally friendly and has little pollution.
[0072] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ -fF f Where d can be 0.001≤d≤0.05, for example, 0.005≤d≤0.05, 0.01≤d≤0.05, 0.015≤d≤0.045, 0.02≤d≤0.04, 0.025≤d≤0.035, 0.03≤d≤0.035, etc. Thus, the positive electrode active material includes the M1 element of this content, which can form a dense and uniform doping layer on the surface of the positive electrode active material, effectively blocking the intrusion of water vapor from the surface of the positive electrode active material to the bulk phase, and improving the structural stability of the material. At the same time, during the high-voltage charging process, the doping layer of this composition can also inhibit the precipitation of lattice oxygen and the penetration of electrolyte into the material, improve the structural stability of the material, and thus improve the capacity retention rate of the battery containing it.
[0073] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F fThe content of the medium rare earth element M1 and Mn satisfies the following relationship: 0.005≤d / c≤0.05, for example, 0.01≤d / c≤0.05, 0.015≤d / c≤0.045, 0.02≤d / c≤0.04, 0.025≤d / c≤0.035, 0.03≤d / c≤0.035. The ratio d / c of the rare earth element M1 to Mn in the positive electrode active material is within the above range, which can reduce the rare earth element agglomeration on the surface of the positive electrode active material to form a mixed phase due to insufficient solid solubility between the rare earth element and Mn, and reduce the probability of not being able to generate a rare earth doping layer due to insufficient rare earth elements, which is conducive to the rare earth element forming a dense and uniform rare earth doping layer on the surface of the positive electrode active material, effectively blocking the invasion of water vapor from the surface of the positive electrode active material to the bulk phase, and can also inhibit the precipitation of lattice oxygen and the penetration of electrolyte into the bulk phase, thereby improving the air stability and cycle stability of the positive electrode active material, thereby improving the capacity retention rate of the battery containing it. In other embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f The content of the medium rare earth element M1 and Mn satisfies the following relationship: 0.01≤d / c≤0.03, which is beneficial to improving the air stability and cycle stability of the positive electrode active material, thereby improving the capacity retention rate of the battery containing it.
[0074] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f Wherein M2 includes at least one of B, Mg, Al, Si, K, Ca, Ga, Ge, Se, Rb, Sr, In, Sn, Sb, Te, Sc, Ti, V, Cr, Co, Cu, Zn, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, Hf, Ta, W, Re, Os, Ir, Pt and Au. Specifically, in the positive electrode active material, the element M2 is uniformly distributed in its bulk phase, and M2 can form a strong chemical bond with O in the positive electrode active material, which, on the one hand, inhibits the escape of the Na element in the positive electrode active material from the bulk phase, and on the other hand, stabilizes the structure of the metal layer of the positive electrode active material, reduces the change in the interlayer spacing of the positive electrode active material, reduces the occurrence of phase change, and improves the cycle performance of the positive electrode active material, thereby improving the capacity retention rate of the battery containing it.
[0075] In some embodiments, the positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f Where δ and f satisfy: -0.1≤δ≤0.1, 0≤f≤0.1, for example, -0.09≤δ≤0.09, -0.08≤δ≤0.08, -0.07≤δ≤0.07, -0.06≤δ≤0.06, -0.05≤δ≤0.05, -0.04≤δ≤0.04, -0.03≤δ≤0.03, -0.02≤δ≤0.02, -0.01≤δ≤0.01, -0.01≤δ≤0, 0≤δ≤0.01, etc., 0.01≤f≤0.09, 0.02≤f≤0.08, 0.03≤f≤0.07, 0.04≤f≤0.06, 0.05≤f≤0.06, etc. Specifically, doping the positive electrode active material with this content of F at the oxygen position in the present application can effectively stabilize the oxygen in the positive electrode active material, thereby reducing the structural damage caused by lattice oxygen release in the positive electrode active material, improving the stability of the material, and further improving the capacity retention rate of the battery.
[0076] It should be noted that in the positive electrode sheet, battery or electrical device, since the battery undergoes cycles and other processes, there is a loss of oxygen in the positive electrode active material, so the measured oxygen content 2+δ-f in the positive electrode active material may be less than 2.
[0077] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f1.75≤(a+b+c) / b≤9.5, for example, 1.8≤(a+b+c) / b≤9.5, 1.9≤(a+b+c) / b≤9.4, 2 ≤(a+b+c) / b≤9.3, 2.1≤(a+b+c) / b≤9.2, 2.2≤(a+b+c) / b≤9.1, 2.3≤(a+b+ c) / b≤9, 2.5≤(a+b+c) / b≤8.5, 3≤(a+b+c) / b≤8, 3.5≤(a+b+c) / b≤7.5, 4≤( a+b+c) / b≤7, 4.5≤(a+b+c) / b≤6.5, 5≤(a+b+c) / b≤6, 5≤(a+b+c) / b≤5.5, etc. Specifically, the ratio of the sum of the contents of Ni, Fe and Mn in the above-mentioned positive electrode active material to the Fe content is controlled within the above-mentioned range. On the one hand, the amount of Na ions that can be removed from the positive electrode active material caused by too little variable-valent metal component Fe is reduced, so that the positive electrode active material has an excellent specific capacity; on the other hand, the amount of Fe that migrates to the Na ion layer due to excessive Fe content in the positive electrode active material and affects the deintercalation of Na ions is reduced, thereby improving the cycle performance of the positive electrode active material, thereby improving the capacity retention rate of the battery containing it.
[0078] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Ni a Fe b Mn c M1 d M2 e O 2+δ-f F f 0.8<x≤1.0, the phase of the positive electrode active material includes O3 phase, the space group includes R3m, and the interlayer spacing is 0.53nm-0.55nm. For example, x can be 0.82-1.0, 0.85-0.95, 0.88-0.90, etc., and the interlayer spacing can be 0.53nm-0.545nm, 0.535nm-0.54nm, 0.536nm-0.539nm, etc. Specifically, when x is within the above range, the Na content of the positive electrode active material of the formed O3 phase is high, and more Na ions can be released, so that the capacity of the battery is high.
[0079] In some embodiments of the present application, 0.6≤x≤0.8, the phase of the positive electrode active material includes a P2 phase, the space group includes P63 / mmc, and the interlayer spacing is 0.54nm-0.57nm. For example, x can be 0.6-0.78, 0.65-0.75, 0.68-0.7, etc., and the interlayer spacing can be 0.54nm-0.565nm, 0.545nm-0.56nm, 0.55nm-0.555nm, etc. Specifically, when x is within the above range, the interlayer spacing of the positive electrode active material of the P2 phase formed is large, which can improve the transmission rate of Na ions and maintain the integrity of the layered structure, so that the battery has excellent rate performance and cycle performance.
[0080] It should be noted that the characterization methods of the phase state, space group and interlayer spacing of the positive electrode active material in the present application can be X-ray diffraction, scanning electron microscopy, transmission electron microscopy, etc. Specifically, in the X-ray diffraction spectrum, the characteristic peak in the range of 40.5° to 42.5° indicates that the positive electrode active material is an O3 phase, and the space group includes R3m, and the characteristic peak in the range of 48° to 50° indicates that the positive electrode active material is a P2 phase, and the space group includes P63 / mmc. The interlayer spacing of the positive electrode active material of the above O3 phase can be calculated by the (003) peak position of the X-ray diffraction; the interlayer spacing of the positive electrode active material of the above P2 phase can be calculated by the (002) peak position of the X-ray diffraction.
[0081] In some embodiments of the present application, the pH value of the soaking solution of the positive electrode active material is less than or equal to 13, for example, the pH value of the soaking solution of the positive electrode active material can be 7-13, 7.2-13, 7.5-13, 8-13, 8.5-13, 9-13, 10-12.9, 10.5-12.7, 11.0-12.7, 11.2-12.5, 11.5-12.3, 11.7-12.0, etc. The pH value of the soaking solution of the positive electrode active material is controlled within the above range, which can reduce the generation of gel during the slurry adjustment process and facilitate the subsequent slurry adjustment and coating of the positive electrode active material. In other embodiments of the present application, the pH value of the soaking solution of the positive electrode active material is less than or equal to 12.7, for example, the pH value of the soaking solution of the positive electrode active material is 11.0≤pH≤12.7.
[0082] Specifically, the pH value of the immersion solution of the positive electrode active material can be measured by the following method:
[0083] The positive electrode active material is dispersed in pure water and soaked, and the soaking liquid is obtained by filtering, and the soaking liquid is measured and titrated with a standard hydrochloric acid solution.
[0084] In some embodiments of the present application, D of the positive electrode active material v 50 is 3 μm-30 μm, for example, Dv 50 can be 3 μm-29 μm, 4 μm-28 μm, 5 μm-15 μm, 6 μm-14 μm, 8 μm-13 μm, 9 μm-12 μm, 10 μm-11 μm, etc. In other embodiments of the present application, the D of the positive electrode active material v 50 is 5μm-15μm.
[0085] In this application, D v 50 refers to the particle size corresponding to when the cumulative volume distribution percentage reaches 50%, for example, with reference to the standard GB / T 19077-2016, and measured using a laser particle size analyzer (such as Malvern Master Size 3000).
[0086] In some embodiments of the present application, the specific surface area of the positive electrode active material is 0.1 m 2 / g-5m 2 / g, for example, the specific surface area of the positive electrode active material can be 0.1m 2 / g-4.5m 2 / g,0.2m 2 / g-4m 2 / g,0.3m 2 / g-3m 2 / g,0.5m 2 / g-2.5m 2 / g,1m 2 / g-2m 2 / g, 1.2m 2 / g-1.8m 2 In some other embodiments of the present application, the specific surface area of the positive electrode active material is 0.3 m 2 / g-3m 2 / g.
[0087] In the present application, the specific surface area of the positive electrode active material can be tested by referring to the following method: using the American Micromeritics multi-station fully automatic specific surface area and pore analyzer GeminiVII2390, take about 7g of the sample and put it into a 9cc long tube with a bulb, degas at 200℃ for 2h, and then put it into the main unit for testing to obtain the BET (specific surface area) data of the positive electrode active material.
[0088] In some embodiments of the present application, the tap density of the positive electrode active material is 1 g / cm 3 -3g / cm 3 For example, the tap density of the positive electrode active material can be 1 g / cm 3 -2.8g / cm 3 , 1.5g / cm 3 -2.5g / cm3 , 1.7g / cm 3 -2.4g / cm 3 , 1.8g / cm 3 -2.g / cm 3 In some other embodiments of the present application, the tap density of the positive electrode active material is 1.5 g / cm 3 -2.5g / cm 3 .
[0089] In this application, tap density refers to the mass per unit volume of the powder in the container after being tapped under specified conditions. The tap density of the positive electrode active material is determined as follows:
[0090] Load the weighed positive electrode active material into the measuring cylinder of the vibration device, and fix the measuring cylinder on the support. Turn the cam, and the directional rod drives the support to slide up and down and hit the anvil. Vibrate 250±15 times per minute for 12 minutes. Measure the volume of the positive electrode active material in the measuring cylinder. The ratio of the mass of the positive electrode active material to the volume is the tap density of the positive electrode active material.
[0091] The calculation formula of tap density is: ρbt=m0 / V
[0092] Where, ρbt is the tap density, g / cm 3
[0093] m0——mass of positive electrode active material, g
[0094] V——Volume of positive electrode active material after compaction (volume of measuring cup), cm 3 .
[0095] In some embodiments of the present application, the compaction density of the positive electrode active material at a pressure of 300 MPa is 3.0 g / cm 3 -4.0g / cm 3 For example, the compaction density of the positive electrode active material at a pressure of 300 MPa can be 3.0 g / cm 3 -3.9g / cm 3 , 3.1g / cm 3 -3.8g / cm 3 , 3.2g / cm 3 -3.7g / cm 3 , 3.3g / cm 3 -3.6g / cm 3 , 3.4g / cm 3 -3.5g / cm 3 wait.
[0096] In some embodiments of the present application, the compaction density refers to the compaction density of the electrode after the material is made into an electrode. Compaction density = surface density / (thickness of the electrode after rolling - thickness of the current collector). Specifically, the compaction density of the positive electrode active material under a pressure of 300 MPa is determined as follows:
[0097] Take the rolled electrode, cut off an area with a circular or square cutter of area s, measure the thickness as a, and weigh it as m1, wash the positive electrode material with a mixture of acetone and alcohol and blow it dry, weigh the remaining aluminum foil weight m2, and measure the thickness of the aluminum foil as b. The difference between the two weights is divided by the area s of the circle or square to calculate the surface density, that is, surface density = (m1-m2) / s. The surface density divided by the thickness difference is the compacted density, that is, compacted density = (m1-m2) / [s(ab)].
[0098] Specifically, when the D of the positive electrode active material of the present application is v 50. When at least one of the specific surface area, tap density and compaction density under a pressure of 300 MPa is within the above range, the conduction distance in the positive electrode active material is small and the surface side reactions are small, which promotes the positive electrode active material to exert its gram capacity and improves the capacity retention rate of the battery containing it.
[0099] The second aspect of the present application provides a method for preparing the positive electrode active material according to the first aspect, comprising:
[0100] S100: Mix Na source, Ni source, Fe source, Mn source, M1 source and M2 source to obtain a precursor
[0101] In some embodiments of the present application, the Na source, the Ni source, the Fe source, the Mn source, the M1 source and the M2 source are mixed according to the above-mentioned positive electrode active material composition.
[0102] It should be noted that the Na source, Ni source, Fe source, Mn source, M1 source and M2 source in the present application are conventional materials in the field, and those skilled in the art can select them according to actual conditions. For example, the Na source may include at least one of Na2CO3, NaHCO3, NaOH and Na2O2; the Ni source may include NiO; the Fe source may include at least one of FeO, Fe2O3 and Fe3O4; the Mn source may include at least one of Mn2O3, Mn3O4, MnO and MnO2; the M1 source may include at least one of the oxide of M1, the salt containing M1 and other compounds; the M2 source may include at least one of the oxide of M2, the salt containing M2 and other compounds.
[0103] It should be noted that if it is necessary to dope the positive electrode active material with the element F, at least one of the Na source, Ni source, Fe source, Mn source, M1 source and M2 source adopts at least one of its corresponding fluoride-containing salts and other compounds, such as sodium fluoride, nickel fluoride, iron fluoride, manganese fluoride, M1 fluoride (fluoride salt of M1) and M2 fluoride (fluoride salt of M2).
[0104] S200: calcining the precursor
[0105] In some embodiments of the present application, the precursor obtained above is placed in a muffle furnace and calcined in an air atmosphere, and then cooled to room temperature and mechanically crushed to obtain the positive electrode active material, wherein the calcination temperature can be 600℃-1200℃, for example, it can be 600℃-1100℃, 700℃-1000℃, 800℃-900℃, etc., and the insulation time is 10h-20h, for example, it can be 10h-19h, 11h-18h, 12h-17h, 13h-16h, 14h-15h, etc.
[0106] In addition, as needed, the precursor can be pre-calcined and kept warm before calcining the precursor. The pre-calcination temperature can be 600℃-900℃, for example, 600℃-850℃, 650℃-800℃, 600℃-750℃, 550℃-700℃, 500℃-650℃, 550℃-600℃, etc. The insulation time is 10h-20h, for example, 10h-19h, 11h-18h, 12h-17h, 13h-16h, 14h-15h, etc.
[0107] Therefore, the solid phase method can be used to prepare the positive electrode active material with excellent air stability and cycle stability, thereby improving the capacity retention rate of the battery.
[0108] The third aspect of the present application provides another method for preparing the positive electrode active material described in the first aspect, comprising:
[0109] Sa: Mix Ni source, Fe source, Mn source, M1 source and M2 source with water to obtain a mixed solution
[0110] In some embodiments of the present application, a Ni source, a Fe source, a Mn source, a M1 source and a M2 source are mixed with water according to the above-mentioned positive electrode active material composition to obtain a mixed solution.
[0111] It should be noted that the Ni source, Fe source, Mn source, M1 source and M2 source in the present application are conventional materials in the field, and those skilled in the art can select them according to actual conditions. For example, the Ni source may include at least one of nickel chloride, nickel sulfate, nickel nitrate and nickel oxalate; the Fe source may include at least one of ferric chloride, ferric sulfate, ferric nitrate and ferric oxalate; the Mn source may include at least one of manganese chloride, manganese sulfate, manganese nitrate and manganese oxalate; the M1 source may include at least one of the chloride, sulfate, nitrate and oxalate of M1; the M2 source may include at least one of the chloride, sulfate, nitrate, oxalate and other compounds of M2.
[0112] Sb: The solution is reacted with a precipitant to obtain a precursor
[0113] In some embodiments of the present application, the solution obtained in step Sa is reacted with a solution containing a precipitant to obtain a precursor, wherein the solution containing a precipitant includes at least one of ammonia water, carbonic acid and oxalic acid.
[0114] Sc: Mix the precursor with the Na source and calcine
[0115] In some embodiments of the present application, the obtained precursor and the Na source are mixed according to the above-mentioned positive electrode active material composition, ball-milled or mechanically stirred to mix evenly, placed in a muffle furnace for calcination, and then cooled to room temperature and mechanically crushed to obtain the positive electrode active material, wherein the calcination temperature is 600°C-1200°C, for example, it can be 700°C-1100°C, 800°C-1000°C, 900°C-950°C, etc., the calcination atmosphere can be air or oxygen atmosphere, and the insulation time is 10h-20h, for example, it can be 10h-19h, 11h-18h, 12h-17h, 13h-16h, 14h-15h, etc.
[0116] It should be noted that, according to needs, before the precursor and the Na source are mixed and calcined, the precursor Na source can be pre-calcined and kept warm in advance, and the pre-calcination temperature can be 600°C-900°C, for example, 600°C-850°C, 650°C-800°C, 600°C-750°C, 550°C-700°C, 500°C-650°C, 550°C-600°C, etc., and the insulation time can be 10h-20h, for example, 10h-19h, 11h-18h, 12h-17h, 13h-16h, 14h-15h, etc. The Na source can include at least one of Na2CO3, NaHCO3, NaOH, and Na2O2.
[0117] It should be noted that if it is necessary to dope the positive electrode active material with the element F, at least one of the Na source, Ni source, Fe source, Mn source, M1 source and M2 source adopts at least one of its corresponding fluoride-containing salts and other compounds, such as sodium fluoride, nickel fluoride, iron fluoride, manganese fluoride, M1 fluoride (fluoride salt of M1) and M2 fluoride (fluoride salt of M2).
[0118] Therefore, the coprecipitation method can be used to prepare the above-mentioned positive electrode active material with excellent air stability and cycle stability, thereby improving the capacity retention rate of the battery.
[0119] The fourth aspect of the present application provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present application, the positive electrode active material prepared by the method described in the second aspect, or the positive electrode active material prepared by the method described in the third aspect.
[0120] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.
[0121] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may include at least one of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh, and carbon-coated aluminum foil.
[0122] The positive electrode active material includes the positive electrode active material described in the first aspect of the present application, the positive electrode active material prepared by the method described in the second aspect, or the positive electrode active material prepared by the method described in the third aspect.
[0123] The positive electrode active material layer may also optionally include a conductive agent and a binder. The conductive agent is used to improve the conductivity of the positive electrode active material layer, and the binder is used to firmly bind the positive electrode active material and the binder to the positive electrode current collector. The present application does not specifically limit the types of the conductive agent and the binder, and they can be selected according to actual needs.
[0124] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; the binder may include at least one of styrene-butadiene rubber (SBR), water-based acrylic resin, carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA) and polyvinyl alcohol (PVA).
[0125] These materials are all commercially available.
[0126] The fifth aspect of the present application provides a battery, which comprises the positive electrode sheet described in the fourth aspect of the present application. Thus, the battery has an excellent capacity retention rate.
[0127] A battery is a battery that can be used again by recharging the active materials after discharge.
[0128] It is understandable that the battery proposed in this application is a sodium ion battery.
[0129] Generally, a battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0130] [Negative electrode]
[0131] In a battery, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0132] The negative electrode current collector may be a conventional metal foil or a composite current collector (for example, a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector may be a copper foil.
[0133] The specific type of the negative electrode active material is not limited, and active materials known in the art that can be used for the negative electrode of sodium ion batteries can be used, and those skilled in the art can choose according to actual needs. As an example, the negative electrode active material may include but is not limited to at least one of sodium metal, carbon material, alloy material, transition metal oxide and / or sulfide, phosphorus-based material, and titanate material. Specifically, the carbon material may include at least one of hard carbon, soft carbon, amorphous carbon, and nanostructured carbon material; the alloy material may include an alloy material formed by at least one of Si, Ge, Sn, Pb, and Sb; the general formula of the transition metal oxide and sulfide is M x N y , wherein M includes at least one of Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V, and N includes O or S; the phosphorus-based material may include at least one of red phosphorus, white phosphorus, and black phosphorus; the titanate material may include Na2Ti3O7, Na2Ti6O 13 、Na4Ti5O 12 、Li4Ti5O 12 At least one of NaTi2(PO4)3. These materials can be obtained through commercial channels.
[0134] The negative electrode active material layer may also optionally include a binder and a conductive agent. The conductive agent is used to improve the conductivity of the negative electrode active material layer, and the binder is used to firmly bind the negative electrode active material and the binder to the negative electrode current collector. The present application does not specifically limit the types of the conductive agent and the binder, and they can be selected according to actual needs.
[0135] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0136] As an example, the binder may include at least one of styrene butadiene rubber (SBR), styrene butadiene rubber (SBCs), water-based acrylic resin, and carboxymethyl cellulose (CMC).
[0137] The negative electrode active material layer may also optionally include a thickener, such as carboxymethyl cellulose (CMC). However, the present application is not limited thereto, and the present application may also use other materials that can be used as thickeners for negative electrode sheets of sodium ion batteries.
[0138] [Electrolyte]
[0139] The electrolyte may include an electrolyte salt and a solvent.
[0140] As an example, the electrolyte sodium salt may include at least one of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate, and sodium bis(trifluoromethylsulfonyl)imide.
[0141] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0142] In some embodiments, the electrolyte further includes additives, such as additives that may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0143] [Isolation film]
[0144] As the above-mentioned isolation membrane, the present application has no special restrictions and any known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected according to actual needs. For example, it can include a single-layer or multi-layer film containing at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0145] The embodiment of the present application has no particular limitation on the shape of the battery, which can be cylindrical, square or any other shape. Figure 1 A square-structured battery 1 is shown as an example.
[0146] In some embodiments, the battery may include an outer packaging for packaging the positive electrode sheet, the negative electrode sheet, and the electrolyte.
[0147] In some embodiments, the outer package may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.
[0148] The positive electrode sheet, the negative electrode sheet and the separator can be wound or laminated to form an electrode assembly. The electrode assembly is packaged in the receiving cavity. The number of electrode assemblies contained in the battery can include one or more, which can be adjusted according to demand.
[0149] In some embodiments, the outer packaging of the battery may include a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.
[0150] The outer packaging of the battery may also include a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0151] In some embodiments, the batteries may be assembled into a battery module. The battery module may contain multiple batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0152] Figure 2 2 is an example of a battery module 2. Figure 2In the battery module 2, the multiple batteries 1 may be arranged in sequence along the length direction of the battery module 2. Of course, they may also be arranged in any other manner. Further, the multiple batteries 1 may be fixed by fasteners.
[0153] The battery module 2 may also include a housing having a storage space, in which a plurality of batteries 1 are stored. In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0154] Figure 3 and 4 The battery pack 3 is used as an example. Figure 3 and 4 The battery pack 3 may include a battery box and a plurality of battery modules 2 disposed in the battery box. The battery box includes an upper box body 4 and a lower box body 5. The upper box body 4 can cover the lower box body 5 and form a closed space for accommodating the battery modules 2. The plurality of battery modules 2 can be arranged in the battery box in any manner.
[0155] The sixth aspect of the present application provides an electrical device, which includes the battery described in the fifth aspect. Specifically, the battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (such as mobile phones, laptops), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships and satellites, and energy storage systems.
[0156] Figure 5 The electrical equipment is used as an example, and the electrical equipment includes a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.
[0157] As another example, the electric device may include a mobile phone, a tablet computer, and a notebook computer. The electric device is usually required to be thin and light, and a battery may be used as a power source.
[0158] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0159] Example 1
[0160]
NaNi 0.2 Fe 0.2 Mn 0.5 La 0.02 Cu 0.08 O2 preparation
[0161] According to the molecular formula stoichiometric ratio, 23.666g of Na2CO3, 6.672g of NiO, 7.131g of Fe2O3, 17.627g of Mn2O3, 1.455g of La2O3 and 2.841g of CuO raw materials (the molar ratio of Na, Ni, Fe, Mn, La and Cu is 1:0.2:0.2:0.5:0.02:0.08) are mixed in the agate ball mill of a planetary ball mill, and the raw materials are ground at a speed of 600r / min, and then the temperature is increased to 950℃ in a muffle furnace at a heating rate of 5℃ / min. After calcination for 15h, the temperature is naturally cooled to room temperature to obtain a black positive electrode active material NaNi 0.2 Fe 0.2 Mn 0.5 La 0.02 Cu 0.08 O2.
[0162]
Preparation of positive electrode
[0163] The NaNi prepared above 0.2 Fe 0.2 Mn 0.5 La 0.02 Cu 0.08 O2, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and N-methylpyrrolidone (NMP) are stirred and mixed evenly in a weight ratio of 60:5:5:30 to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode aluminum foil collector, and the positive electrode sheet is obtained after drying, cold pressing, and slitting.
[0164]
Preparation of negative electrode sheet
[0165] The negative electrode plate is made of metallic sodium.
[0166]
Preparation of electrolyte
[0167] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3 / 7 to obtain a mixed solvent, and then NaPF6 was dissolved in the mixed solvent and stirred evenly to obtain an electrolyte with a sodium salt concentration of 1 mol / L.
[0168]
Isolation film
[0169] Glass fiber is used as the isolation membrane.
[0170] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the prepared electrolyte is injected into the dried secondary battery. After vacuum packaging, standing, formation, and shaping processes, a secondary battery is obtained.
[0171] The secondary batteries containing the positive electrode active materials of Examples 2-24 and Comparative Examples 1-4 are the same as Example 1 except for the different parameters (see Table 1).
[0172] The compositions of the positive electrode active materials in the batteries of Examples 1-24 and Comparative Examples 1-4 of the present application are shown in Table 1.
[0173] Table 1
[0174]
[0175]
[0176] The D of the positive electrode active material in Examples 1-24 and Comparative Examples 1-4 v 50. The specific surface area, tap density, compacted density under a pressure of 300 MPa, pH value of the immersion solution, phase state, space group and interlayer spacing, as well as the capacity and capacity retention rate of the obtained sodium ion battery were characterized. The characterization results are shown in Table 2.
[0177] Performance Testing:
[0178] 1. Phase state, space group and interlayer spacing test of positive electrode active materials: Make an XRD pattern of the positive electrode active material, determine the phase state and space group of the positive electrode active material according to the position of the characteristic peak in the XRD pattern, and calculate the interlayer spacing d of the positive electrode active material according to the position of the (003) peak or (002) peak of X-ray diffraction and the corresponding peak and the formula d = λ / (2sinθ). In the formula d = λ / (2sinθ), the wavelength of the ray is The characteristic peaks in the scanning 2θ angle range of 40.5° to 42.5° indicate that the positive electrode active material is O3 phase, and the space groups include The characteristic peaks scanning the 2θ angle in the range of 48° to 50° indicate that the positive electrode active material is a P2 phase, and the space group includes P63 / mmc.
[0179] 2. D of positive electrode active material v 50 Determination: With reference to GB / T 19077-2016, the determination was carried out using a Malvern Master Size 3000 laser particle size analyzer.
[0180] 3. Determination of tap density: Load the weighed positive electrode active material into the measuring cylinder of the tapping device and fix the measuring cylinder on the support. Turn the cam, and the directional rod drives the support to slide up and down and hit the anvil. Vibrate 250±15 times per minute for 12 minutes. Determine the volume of the positive electrode active material in the measuring cylinder. The ratio of the mass of the positive electrode active material to the volume is the tap density of the positive electrode active material.
[0181] The calculation formula of tap density is: ρbt=m0 / V
[0182] Where, ρbt is the tap density, g / cm 3
[0183] m0——mass of positive electrode active material, g
[0184] V——Volume of positive electrode active material after compaction (volume of measuring cup), cm 3 .
[0185] 4. Compacted density of positive electrode active material under 300MPa pressure: Take the rolled electrode sheet, cut off an area with a circular or square cutter with an area of s, measure the thickness as a, and weigh it as m1, wash the positive electrode material with a mixture of acetone and alcohol and blow it dry, weigh the remaining aluminum foil weight m2, and measure the thickness of the aluminum foil as b. The difference between the two weights is divided by the area s of the circle or square to calculate the surface density, that is, surface density = (m1-m2) / s. The surface density divided by the thickness difference is the compacted density, that is, compacted density = (m1-m2) / [s(ab)].
[0186] 5. Determination of pH value of the soaking solution of the positive electrode active material: disperse the positive electrode active material in pure water and soak it, filter to obtain the soaking solution, and measure the soaking solution and titrate it with standard hydrochloric acid solution.
[0187] 6. Capacity test of positive electrode: make positive electrode, make negative electrode, punch and weigh, select the mass of positive and negative electrode according to the type of positive and negative electrode materials, and then place them in the glove box for 2 hours; assemble the button battery in the glove box, clamp the button battery on the electrochemical test cabinet, and calculate the charge and discharge current according to the test rate (0.2C, 1C, 3C, 5C), current = rate × theoretical gram capacity × (M2-M1) × ω% where: theoretical gram capacity - determined by the theoretical gram capacity of the positive electrode material;
[0188] M2——actual weight of the pole piece;
[0189] M1——average weight of current collector;
[0190] ω%——Actual mass fraction of active substances
[0191] 7. Battery capacity retention rate test:
[0192] Taking Example 1 as an example, at 25°C, the secondary battery was charged at a constant current rate of 0.1C to a charge cut-off voltage of 4.2V, then discharged at 0.1C to 1.5V, left for 5 minutes, and then discharged at a constant current rate of 0.5C to a discharge cut-off voltage of 2.8V, left for 5 minutes, and the battery discharge capacity C0 was recorded at this time. According to this method, the battery was charged and discharged for 500 cycles, and the battery discharge capacity after 500 cycles was recorded as C1.
[0193] The cycle capacity retention rate of the secondary battery = C1 / C0×100%.
[0194] The testing process of the capacity retention rate of the secondary batteries of Examples 2-24 and Comparative Examples 1-4 is the same as above.
[0195] The XRD patterns of the positive electrode active materials of Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG. Figure 6 and Figure 7 As shown, compared with Example 1, the ratio d / c of the rare earth element M1 to Mn in the positive electrode active material in Comparative Example 1 is 0.004, which is less than 0.005, and the peak between 10-20 of the positive electrode active material is not obvious, while the impurity peak between 30-40 is more obvious. It can be seen that too little rare earth element is not conducive to improving the air stability and cycle stability of the positive electrode active material; compared with Example 1, the ratio d / c of the rare earth element M1 to Mn in the positive electrode active material in Comparative Example 2 is 0.06, which is greater than 0.05, and the positive electrode active material has obvious impurity peaks. It can be seen that there are too many rare earth elements and the solid solubility between the rare earth elements and Mn is insufficient, which causes the rare earth elements to agglomerate on the surface of the positive electrode active material to form impurity phases.
[0196] Figure 8 The charge and discharge curve of the sodium ion battery prepared in Example 1 at 0.1C in the first cycle shows that the operating voltage range of the battery is 1.5V-4.2V.
[0197] The capacity retention rate comparison diagram of Example 1 and Comparative Example 4 is shown in Fig. 9 As shown, it can be seen that the capacity retention rate of Example 1 of the present application is significantly better than that of Comparative Example 4.
[0198] Table 2
[0199]
[0200]
[0201] As can be seen from Table 2, in the embodiments of the present application, NiFeMn is used as the main material and is doped with rare earth element M1 and doping element M2 and the ratio of rare earth element M1 to Mn is controlled, which can improve the air stability and cycle stability of the positive electrode active material, thereby improving the capacity retention rate of the battery containing it. Compared with the embodiments, the values of d / c in Comparative Examples 1 and 2 are not within the range of the embodiments of the present application, and the values of the content c of Mn in Comparative Examples 3 and 4 are not within the range of the embodiments of the present application, and the capacity retention rate and capacity of the battery containing it are significantly reduced.
[0202] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material comprises: So x Ni a Feb b Mr c M1 d M2 e O 2+δ-f F f , Wherein, M1 includes rare earth elements, M2 includes at least one of Group IA elements, Group IIA elements, Group IIIA elements, Group IVA elements, Group VA elements, Group VIA elements and transition elements, 0.6≤x≤1.2, 0<a≤0.5, 0<b≤0.4, 0.3≤c≤0.75, 0.001≤d≤0.05, 0≤e≤0.3, -0.1≤δ≤0.1, 0≤f≤0.1, 0.005≤d / c≤0.05, a+b+c+d+e=1.
2. The positive electrode active material according to claim 1, characterized in that The rare earth element includes at least one of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu.
3. The positive electrode active material according to claim 1 or 2, characterized in that: The M2 includes at least one of B, Mg, Al, Si, K, Ca, Ga, Ge, Se, Rb, Sr, In, Sn, Sb, Te, Sc, Ti, V, Cr, Co, Cu, Zn, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, Hf, Ta, W, Re, Os, Ir, Pt and Au.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that 0.01≤d / c≤0.
03.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that The positive electrode active material satisfies at least one of the following conditions: 0.1≤a≤0.4, optional 0.15≤a≤0.3; 0.1≤b≤0.35, which can be 0.15≤b≤0.35; 0.35≤c≤0.6, optionally 0.35≤c≤0.
5.
6. The positive electrode active material according to any one of claims 1 to 5, characterized in that 1.75≤(a+b+c) / b≤9.5, optionally, 2≤(a+b+c) / b≤9.5, more optionally, 2≤(a+b+c) / b≤6.
3.
7. The positive electrode active material according to any one of claims 1 to 6, characterized in that 0.8<x≤1.0, the phase state of the positive electrode active material includes O3 phase, the space group includes R3m, and the interlayer spacing is 0.53nm-0.55nm.
8. The positive electrode active material according to any one of claims 1 to 6, characterized in that 0.6≤x≤0.8, the phase state of the positive electrode active material includes P2 phase, the space group includes P63 / mmc, and the interlayer spacing is 0.54nm-0.57nm.
9. The positive electrode active material according to any one of claims 1 to 8, characterized in that The pH value of the soaking solution of the positive electrode active material is less than or equal to 13. Optionally, the pH value of the soaking solution of the positive electrode active material is less than or equal to 12.
7. More optionally, the pH value of the soaking solution of the positive electrode active material is 11.0≤pH≤12.
7.
10. The positive electrode active material according to any one of claims 1 to 9, characterized in that The positive electrode active material satisfies at least one of the following conditions: The positive electrode active material D v 50 is 3μm-30μm, optional is 5μm-15μm; The specific surface area of the positive electrode active material is 0.1 m 2 / g-5m 2 / g, optional 0.3m 2 / g-3m 2 / g; The tap density of the positive electrode active material is 1 g / cm 3 -3g / cm 3 , optional 1.5g / cm 3 -2.5g / cm 3 ; The compaction density of the positive electrode active material under a pressure of 300 MPa is 3.0 g / cm 3 -4.0g / cm 3 .
11. A method for preparing the positive electrode active material according to any one of claims 1 to 10, characterized in that: include: Mixing a Na source, a Ni source, a Fe source, a Mn source, an M1 source, and an M2 source to obtain a precursor; The precursor is calcined to obtain a positive electrode active material.
12. A method for preparing the positive electrode active material according to any one of claims 1 to 10, characterized in that: include: Mixing a Ni source, a Fe source, a Mn source, a M1 source, and a M2 source with water to obtain a mixed solution; reacting the solution with a precipitant to obtain a precursor; The precursor is mixed with a Na source and then calcined to obtain a positive electrode active material.
13. A positive electrode sheet, characterized in that: The positive electrode plate comprises the positive electrode active material according to any one of claims 1 to 10 or the positive electrode active material prepared by the method according to claim 11 or 12.
14. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 13.
15. An electrical equipment, characterized in that: Comprising the battery of claim 14.
Citation Information
Patent Citations
Positive electrode active material and preparation method thereof, positive electrode plate and sodium ion battery
CN115810748A
Positive electrode active material, method for producing positive electrode active material, positive electrode, nonaqueous electrolyte power storage element, method for manufacturing nonaqueous electrolyte power storage element, and method for using nonaqueous electrolyte power storage element
JP2019145360A
Lithium nickel cobalt manganese oxide composite material grain, method for making the same, and lithium battery using the same
TW201208184A
Positive electrode active material for nonaqueous electrolyte secondary batteries, positive electrode using said positive electrode active material, and secondary battery
WO2018025795A1
Cited By
Sodium-ion battery oxide single-crystal positive electrode material as well as preparation method and application thereof
CN120099640A
